LELANG JABATAN; INTEGRITAS ASN, KINERJA ASN, DAN FRAUD KEPALA DAERAH - Pratomo Cahyo Kurniawan; Siti Zulfa; Lutfiatul Hikmah (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
The election of regional heads is carried out directly by the people and has an impact. The positive impact is that the community is directly involved in voting, while the negative impact is that the election costs are expensive for regional head candidates. Position auctions in several areas have changed meaning. This phenomenon used to carry out unloading and select Government Employees who are considered helpful and choose Government Employees who dare to register for positions with certain rates. This qualitative research uses the technical analysis of observation, and literature study with the method of triangulation of data sources as a test of data validity. The results found that the phenomenon of an auction of positions carried out unprofessionally became a transactional political tool for regional heads. The correlation of expensive political costs with low regional head integrity can trigger the occurrence of job auctions with tariffs. As a result, officials from the auction of positions will only serve their regional heads and think about their interests. This will affect regional transformation, bureaucratic reform, and less-than-optimal public services.